Integrated motor drives - Deng, Xu; Mecrow, Barrie (Institution of Engineering and Technology, 2022)
Optimisation of electric drives for machines and EV requires considering the components as a whole. Integrated systems can be smaller, have greater flexibility, lower cost and higher power density. This book presents recent research and trends in integrated electrical motor drive technology.
Keywords: Electric motors -- Electronic control.; Electric vehicles -- Motors.; elektronické knihy; electronic books